Sosialisasi Pentingnya Pengunaan Masker pada Pembelajaran Tatap Muka pada Masa Pandemi COVID-19 di Sekolah Menengah Atas (SMA) Kota Padang: Socialization of the Importance of the Use of Mask in Face-to-Face Learning During the COVID-19 Pandemic at the Senior High School in Padang City - Dewi Mardiawati; Linda Handayuni; Ririn Afrima Yenni; Claudya Rizki Audina Daulay; Kevin Wahyudi Farhan; Nidno Friani Candra (Jurnal Surya Medika (JSM), 2022)
Coronaviruses (CoV) are a large family of viruses that cause illness ranging from mild to severe. Based on the mayor's circular, all schools in the city of Padang are activated while still observing health protocols. The purpose of this service is to provide understanding to school children about the importance of using masks in the community according to the recommendations for implementing health protocols as an effort to increase awareness about the importance of early prevention of the COVID-19 virus. The method of activity used in this community service activity is the dissemination of the importance of using masks during the COVID-19 pandemic as an effort to implement health protocols in order to create prevention of the Covid-19 virus in the community in dealing with the current pandemic situation. The implementation is to do presentations at school by providing socialization to students/school children and also providing brochures so that students understand the importance of using masks while carrying out learning at school. Basically, students really understand the importance of wearing masks during the COVID-19 pandemic, especially in the school environment. But sometimes there are still many students who don't want to wear masks on the grounds that it's hard to breathe, it's hot and they are in the room for a long time. Of the 10 high schools that will be socialized, only 5 high schools are willing to do the socialization, namely: SMA SIMA, PGRI 3, SMAN 6, PGAI, and Development. This service activity can increase the knowledge and understanding of high school students/children about the importance of using masks during the COVID-19 pandemic. So that in the future the quality of people's lives will improve and the spread of COVID-19 can be reduced.